PARANASAL SINUS PATHOSES ON CONE BEAM COMPUTED TOMOGRAPHY - Esin Bozdemir; Özlem Görmez; Derya Yıldırım; Ayşe Aydoğmuş Erik (Journal of Istanbul University Faculty of Dentistry, 2016)
Purpose: The aim of this study was to investigate paranasal sinus pathoses detected on cone-beam computed tomography (CBCT) in an adult population. Patients and Methods: Three observers retrospectively inspected 353 consecutive CBCT scans obtained in a dentomaxillofacial radiology department for paranasal sinus pathoses. Descriptive statistics and chi-square tests were used to determine the prevalence of categorical parameters. Results: The age of the patients ranged from 18 to 85 years (mean 41.27±16.76). There were 172 (48.7%) females and 181 (51.3%) males. There was a significant difference between the genders (p=0.02), with males (53.5%) having more sinus pathoses than females (46.5%). When the left and right sinuses were considered together, pathoses were most commonly seen in the maxillary sinuses (57.1%), followed by the ethmoid (53.7